47 STEMI referrals from the community versus the emergency department, the west of Ireland experience. (7th October 2015) - Cuddy, S; Adeel, Y; Walsh, R; Sharif, F; Hynes, B; McNeill, B; Nash, P; Daly, K; Crowley, J
Abstract : Optimal reperfusion in STEMI is the key goal of the National ACS programme. Some of the aims of the programme are reperfusion time (RT) of <120 min, in particular Primary PCI (PPCI) as the method of reperfusion in 80% of STEMIs, establishing diagnosis in the pre-hospital phase, a diagnosis to door time (DDT) of <90 min. Aim: The aim of this study was to compare patients with a STEMI referred directly from the community, either by the Ambulance service or GP, with the referrals from outside hospitals ED and UHG ED relating to the goals listed above. Method: We used the heart-code database in UHG to identify all Code STEMI patients in the West of Ireland in 2014. Results: In 2014 there were 324 Code STEMI referrals to UHG (18.8% female, average age 63), 311 (95.9%) of the referrals underwent angiography. Of all the Code STEMI patients 262 (80.8%) had a confirmed diagnosis of STEMI, either clinically or angiographically. Of 262 STEMI patients 108 were diagnosed in the prehospital phase and referred directly to the PCI-centre at UHG. In 64 cases (59.2%) ambulances bypassed non-PCI centres. The mean DDT was 68 min (SD 32.4). 24% had a DDT >90 min. There were 112 STEMI patients transferred from outside hospitals, 52 of the patients received thrombolysis prior to transfer. Excluding the later, DDT was 170 min (SD 128.7), DDT >90 mins in 63.7% of cases. The difference in DDT between the groups is statistically significant (p < 0.001). Of the STEMI cases directly referred from the community 98 (90.7%) had PPCI. The mean RT was 118 min (SD 54.8), RT > 120 min in 40.6%. 48 (42.8%) of the patients transferred from an outside hospital had PPCI, RT was 179 min (SD 120), RT >120 min in 63.8%. The difference in RT is statistically significant (p = 0.009). The ED in UHG referred 38 STEMI patients. Mean door to ECG time was 32 min (SD 7.9), 62.1% were outside the recommended 10 min. 30 (78.9%) patients had PPCI, mean RT was 127.5 min (SD 100.1), 66% of cases were outside recommended door to reperfusion time. The difference in RT between the ED and community group was significant (p = 0.013). The difference in RT was not significant when compared to the group referred from outside hospitals (p = 0.80). Conclusion: The findings above clearly demonstrate the ACS programme in the West of Ireland has been successful in achieving its goals in direct transfers from the community, of 80% PPCI in STEMI with a mean RT <120 in 2014. This STEMI cohort shows the significant delay encountered when patients are initially admitted to ED prior to transfer to the Cath Lab, whether in the PCI centre or outside hospitals. Certain time delays are often unavoidable, for example unstable patients that require initial management in Resus. However the findings here emphasise the need for improvement in key areas, such as Door to ECG time in ED.